Nonserogroup-1 Legionella pneumophila Pneumonia: Navigating Diagnostic Challenges - Lara K. Rotter; Julian A. Villalba; Claressa E. Lucas; Melisa J. Willby; Marwan M. Azar (Annals of Internal Medicine: Clinical Cases)
A 59-year-old woman with newly diagnosed immune thrombocytopenia treated with steroids and rituximab presented with a cavitary lung lesion. Extensive work-up, including bronchoalveolar lavage and transthoracic lung biopsy, were unrevealing. Molecular testing on lung tissue ultimately diagnosed nonserogroup-1 Legionella pneumophila, underscoring the utility of advanced diagnostics in clinical conundrums.